IFC’s Experience with Inclusive Business : An Assessment of IFC’s Role, Outcomes, and Potential Scenarios - Independent Evaluation Group (World Bank, Washington, DC, 2020)
This evaluation is a corporate-level assessment of the role and effectiveness of IFC in its support to its clients’ inclusive business models. It also identifies implications and options for IFC’s future support to inclusive business. The evaluation uses a two-pronged approach based on: (i) a review of IFC’s entire portfolio (comparing inclusive business projects with the rest of IFC’s portfolio), integrating IEG’s relevant evaluative evidence across different sectors and themes; and (ii) a focus on the agribusiness sector. Based on the findings of this evaluation, the report concludes with three options for IFC to consider: (i) Option 1: Keep the current approach, (ii) Option 2: Upgrade IFC’s current approach to an “operational framework”, and (iii) Option 3: Design a corporate strategy toward inclusive business.